Avoiding Deadline Decay Under Transient Overloads - Swim, B.; Taylı, Murat; Benmaiza, M.; Woodward, M. (IEEE, 1995)
Deadline scheduling policies based on stochastic computation times perform well in average but fail in presence of transient overloads, causing already scheduled tasks to miss their deadline. This paper presents an approach using medium-term scheduling policies to cope with the problem of transient overload in dynamic real-time systems. The proposed approach has been implemented in a Real-Time Distributed Operating System (RTDOS) running on a Transputer network.
Keywords: Processor scheduling; Dynamic scheduling; Real time systems; Stochastic processes; Operating systems; Computerized monitoring; Condition monitoring; Topology; Educational institutions; Adaptive systems; scheduling; operating systems (computers); network operating systems; real-time systems; deadline decay avoidance; transient overloads; deadline scheduling policies; stochastic computation; dynamic real-time systems; Real-Time Distributed Operating System; Transputer network